The impact of quasi-markets on processes and factors affecting the costs of contracting. (3rd March 2016) - Hurri, Jaana; Vuori, Jari; Liddle, Joyce; Allen, Pauline
ABSTRACT: The aim of this paper is to ascertain the impact of quasi-markets on contracting processes and factors affecting the costs of contracting in Finnish health care in the specific case of laboratory services. By means of a comparative case analysis, we ascertained the changes in organizational contracting practices and identified the actions affecting the transaction costs of contracting in the case of an autonomous municipal enterprise laboratory compared with the same laboratory as a hierarchically run municipal unit. The research was conducted during the years 2007–2011. The results suggest that introducing quasi-markets into laboratory services increased the cost factors of contracting; and had a negative impact on the laboratories' willingness to create new market relationships.